PENGARUH QUALITY OF WORKLIFE TERHADAP WORK ENGAGEMENT DIMEDIASI JOB BURNOUT (STUDI PADA KARYAWAN GEN-Z PT. XYZ) - Alfani Maulidya Kamal; Eman Sulaeman (Target : Jurnal Manajemen Bisnis, 2026)
Work engagement has become a critical issue in the manufacturing sector, particularly among Generation Z employees who tend to prioritize work-life balance, psychological well-being, and supportive work environments. High production targets, shift work systems, and demanding workloads may increase job burnout, thereby reducing employees’ work engagement. This study aims to examine the effect of the quality of work life on work engagement, with job burnout serving as a mediating variable, among Generation Z employees at PT XYZ. A quantitative approach with a survey method was employed. The study involved 100 respondents selected using purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 4. The findings reveal that quality of work life has a significant negative effect on job burnout, indicating that a better work environment, balanced workload, and supportive social relationships reduce employees’ burnout levels. Job burnout also has a significant negative effect on work engagement, whereas quality of work life has a significant positive effect. Furthermore, job burnout significantly mediates the relationship between quality of work life and work engagement, suggesting that improvements in employees’ quality of work life enhance work engagement both directly and indirectly by reducing burnout. These findings support the Job Demands–Resources (JD-R) Theory and highlight the importance of developing organizational strategies that improve employees’ quality of work life, thereby reducing burnout and strengthening sus- tainable work engagement among Generation Z employees in the manufacturing sector.